GPCRs in pancreatic adenocarcinoma: Contributors to tumour biology and novel therapeutic targets - Sriram, Krishna (Br J Pharmacol, 2020)
Pancreatic cancer has one of the highest mortality rates (5‐year survival ~9%) among cancers. Pancreatic adenocarcinoma (PAAD) is the most common (>80%) and the most lethal type of pancreatic cancer. A need exists for new approaches to treat pancreatic adenocarcinoma. GPCRs, the largest family of cell‐surface receptors and drug targets, account for ~35% of approved drugs. Recent studies have revealed roles for GPCRs in PAAD cells and cells in the tumour micro‐environment. This review assesses current information regarding GPCRs in PAAD by summarizing omics data for GPCRs expression in PAAD. The PAAD “GPCRome” includes GPCRs with approved agents, thereby offering potential for their repurposing/repositioning. We then reviewed the evidence for functional roles of specific GPCRs in PAAD. We also highlight gaps in understanding the contribution of GPCRs to PAAD biology and identify several GPCRs that may be novel therapeutic targets for future work in search of GPCR‐targeted drugs to treat PAAD tumours.